2021
DOI: 10.1371/journal.pone.0247554
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual hygiene management practices and associated health outcomes among school-going adolescents in rural Gambia

Abstract: Inadequate menstrual hygiene management (MHM) practices have been associated with adverse health outcomes. This study aimed to describe MHM practices among schoolgirls from rural Gambia and assess risk factors associated with urogenital infections and depressive symptoms. A cross-sectional study was conducted among adolescent schoolgirls in thirteen schools in rural Gambia. A questionnaire was used to collect information on socio-demographics, MHM practices and clinical symptoms of reproductive and urinary tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 45 publications
(91 reference statements)
1
18
0
Order By: Relevance
“…In turn, the lack of adequate menstrual management facilities in public spaces contributes to the invisibilization and taboo of menstruation. Besides, not being able to manage menstruation reinforces and perpetuates MI and may lead to health risks [ 18 , 59 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the lack of adequate menstrual management facilities in public spaces contributes to the invisibilization and taboo of menstruation. Besides, not being able to manage menstruation reinforces and perpetuates MI and may lead to health risks [ 18 , 59 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…All participating schools ( n = 19) were asked to create lists of female students that were 13 years and older from grades 5–12, all girls from this list were asked their menstrual status, and those that had started menstruating were included in the survey. Sample size calculations for the individual cross-sectional studies are described elsewhere [ 6 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies across low and middle income countries (LMICS) suggest more than 50% of girls have inadequate menstrual hygiene management (MHM) practices, with higher proportions in rural areas [ 1 , 2 , 3 , 4 ]. Poor MHM may lead to school absenteeism, disengagement or withdrawal from school [ 1 , 5 ], reproductive problems, urinary tract infections [ 5 , 6 , 7 ], withdrawal from social gatherings, and unnecessary restrictions to the daily routine [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in The Gambia (MRC-PHIND) among school girls in the Kiang region suggested challenges related to MH at home or school could be associated with negative health outcomes and school absenteeism [ 26 , 27 ]. The study showed that students (boys and girls) had poor knowledge about menstruation, largely due to the need for secrecy and cultural beliefs [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in The Gambia (MRC-PHIND) among school girls in the Kiang region suggested challenges related to MH at home or school could be associated with negative health outcomes and school absenteeism [ 26 , 27 ]. The study showed that students (boys and girls) had poor knowledge about menstruation, largely due to the need for secrecy and cultural beliefs [ 26 , 27 ]. Findings from a mixed methods approach suggested that lack of knowledge of menstruation and adequate absorbent materials led to embarrassment and fear of teasing, and this, together with pain and poor school water sanitation and hygiene (WASH) facilities contributed to school absenteeism.…”
Section: Introductionmentioning
confidence: 99%